2014
DOI: 10.1186/1756-8722-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Romidepsin for the treatment of relapsed/refractory peripheral T-cell lymphoma: pivotal study update demonstrates durable responses

Abstract: BackgroundRomidepsin is a structurally unique, potent, bicyclic class 1 selective histone deacetylase inhibitor approved by the US Food and Drug Administration for the treatment of patients with cutaneous T-cell lymphoma who have received ≥ 1 prior systemic therapy and patients with peripheral T-cell lymphoma (PTCL) who have received ≥ 1 prior therapy. Approval for PTCL was based on results (n = 130; median follow-up, 13.4 months) from the pivotal study of romidepsin for the treatment of relapsed/refractory PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(161 citation statements)
references
References 29 publications
8
153
0
Order By: Relevance
“…The AE profile for patients with AITL was consistent with the known profile for romidepsin in patients with all subtypes of PTCL 11, 12, 13. The most common grade ≥3 AEs were thrombocytopenia (30%, all drug‐related), neutropenia (22%, all drug‐related), infections (all types pooled; 22%, 4% drug‐related) and anemia (15%, 7% drug‐related).…”
Section: Tablesupporting
confidence: 66%
“…The AE profile for patients with AITL was consistent with the known profile for romidepsin in patients with all subtypes of PTCL 11, 12, 13. The most common grade ≥3 AEs were thrombocytopenia (30%, all drug‐related), neutropenia (22%, all drug‐related), infections (all types pooled; 22%, 4% drug‐related) and anemia (15%, 7% drug‐related).…”
Section: Tablesupporting
confidence: 66%
“…histone deacetylases [HDAC]), proteins with enzymatic activity that either add or remove post-translational modifications respectively to histone proteins. Vorinostat is the first HDAC inhibitor approved for treatment of relapsed cutaneous T-cell lymphoma [Duvic et al 2007;Grant et al 2007;Mann et al 2007] and along with other HDAC inhibitors such as romidepsin and panobinostat, is in clinical trials for other types of lymphoma and for multiple myeloma [Dimopoulos et al 2013;Coiffier et al 2014;Straus et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that FK228 is a novel HDACi that could effectively inhibit the proliferation of tumour cells (Coiffier et al 2014;Mummaneni & Shord 2014;Wei et al 2014) and suffer more cytotoxicity in cancer cells than normal cells (Kasman et al 2007;Emanuele et al 2008). This study showed that FK228 treatment has a concentration-and time-dependent effect on the morphology and growth of porcine foetal fibroblast cells; and these findings are consistent with the results reported previously (Savickiene et al 2006;Hoshino et al 2008).…”
Section: Discussionmentioning
confidence: 91%